Double strain probiotic effect on Helicobacter pylori infection treatment: A double-blinded randomized controlled trial - Mehdi Haghdoost; Sepehr Taghizadeh; Majid Montazer; Parinaz Poorshahverdi; Ali Ramouz; Sanam Fakour (Babol University of Medical Sciences, 2017)
Background: A decreased rate of successful helicobacter pylori (H.pylori) infection treatment has revealed serious demand for more effective regimens to eradicate infection. Therefore, probiotics have recently been considered to increase the rate of antibiotic regimens efficacy in H. pylori infections. In current randomized controlled trial, we evaluated the effect of double strain probiotic combination with standard triple therapy (STT), in the eradication rate of H. pylori infection. Methods: In current randomized placebo-control study, all patients (176 subjects) underwent the STT for 10 days. However, the study group received triple therapy for the eradication of H. pylori with supplement of Lactobacillus probiotic for 4 weeks and placebo was administered to control group, as well. Adverse effects of the antibiotic regimen were recorded for all patients. Six weeks after the cessation of probiotic intake, all patients underwent H. Pylori with fecal antigen of test, followed by a recurrence evaluation six months later. Results: There was no significant difference in demographic data and presenting symptoms between the study groups. The eradication rate of H. pylori infection was significantly higher in probiotic group (78.4%), compared to that of placebo group (64.8%) (P=0.033). In addition, adverse events were significantly less prevalent in patients that received probiotic (P=0.047). Nonetheless, there was no significant difference in terms of infection recurrence during a 6-month follow-up (P=0.07). Conclusion: Double strain probiotic in combination with STT increased the eradication rate of H. pylori infection, while the adverse events due to antibiotic therapy decreased